Predicting Academic Performance with Applying Data Mining Techniques (Generalizing the results of two Different Case Studies) - Rozita Jamili Oskouei; Mohsen Askari (Universitas Sriwijaya, 2014)
Several research works are attempted to predict students academic performance and assess the evaluating students knowledge or detecting students’ weakness and probability of failure in final semester examinations. However, several factors affect the performance of students in different countries or even in different states of one country. Therefore, understanding these factors and analyzing the effects of each one of those factors in each country, is necessary for improving instructors’ decisions in selecting the best teaching method for helping weak students or increasing performance of other students. This study is motivated to study the students’ academic performance in high school and bachelor degree studies in Iran and comparing these analysis results with the similar study’s results in India.